Some aspects of the Reproductive Biology of Barbus barbulus Heckel, 1847, from Karoon river, Iran - Mortezavizadeh, Seyed Abdolsaheb; Hashemi, Seyed Ahmadreza; Eskandary, Golam Reza (Iraqi Journal of Aquaculture, 2022)
The present study was carried out from December 2007, during which to November 2008 more than 210 fish (Barbus barbulus) were caught and measured, including, 57 males, 64 females and 89 immature fishes. Maximum and minimum total lengths were 885 mm and 210 mm respectively. Maximum and minimum total weight was 8460 g and 99 g respectively. The length-weight relationship was Y=0.00002 L2.90 (n=57, R2=0.85) for males, Y=0.000002 L3.22 (n=64, R2=0.87) for females and Y=0.00005 L2.96 (n=210, R2 =0.90) for total fishes, these results showed isometric growth of the studied fish. The mean value of Gonado- Somatic Index (GSI) for the male and female were 1.58 ± 0.41 and 1.85 ± 0.22 respectively. For both sexes, the highest GSI value was in March and the lowest in December. GSI and maturity stages indicated that spawning time was during March to April. The mean size at first sexual maturity (Lm) was 380-430 mm for males and 470-520 mm for females.